First-Line Chemo-Immunotherapy for Extensive-Stage Small-Cell Lung Cancer: A United States-Based Cost-Effectiveness Analysis - Liu, Qiao; Luo, Xia; Yi, Lidan; Zeng, Xiaohui; Tan, Chongqing (Frontiers in Oncology, 2021)
Objective This study aimed to assess the cost-effectiveness of two recently approved first-line chemo-immunotherapies [atezolizumab combined with etoposide and platinum (AEP) and durvalumab combined with etoposide and platinum (DEP)] for patients with extensive-stage small-cell lung cancer (ES-SCLC) in the United States. Material and Methods A Markov model was built to compare the cost and effectiveness of AEP, DEP and etoposide plus platinum (EP) over a 10-year time horizon. Clinical efficacy and safety data were extracted from the IMpower 133 and CASPIAN trials. Health state utilities were obtained from published literature. Costs were collected from an US payer perspective. Deterministic and probabilistic sensitivity analyses were used to explore the uncertainty bound to model parameters. Results For the model cohort of adult patients with treatment-naive ES-SCLC, AEP was associated with marginal improved quality adjusted life years (QALYs) by 0.016 and reduced costs by $5,737 compared with DEP. When comparing the two chemo-immunotherapies with EP chemotherapy, AEP and DEP increased the QALYs by 0.162 QALYs and 0.146, respectively. However, both chemo-immunotherapies were associated with substantially health costs than EP, resulting in ICERs of $382,469 per QALY and $464,593 per QALY, respectively. Conclusion In this cost-effectiveness study, first-line AEP represented a dominant treatment strategy compared with DEP. Despite neither first-line AEP nor first-line DEP was cost-effective compared with EP chemotherapy, AEP was able to provide a more efficient balance between incremental cost and QALY than DEP. When new combination therapies with remarkable effect become pivotal in the first-line treatment, the price reduction of these drugs may be essential to achieving cost-effectiveness.